Forma urbana e mobilidade sustentável: Evidências de cidades brasileiras - Rafael Henrique Moraes Pereira; Jo\~ao Pedro Figueira Amorim Parga; Marcus Saraiva; Jo\~ao Pedro Bazzo; Diego Bogado Tomasiello; Luiz Pedro Silva; Vanessa Gapriotti Nadalin; Rogério Jerônimo Barbosa (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– The spatial organization of cities has important implications for sustainable urban development. Several studies have analyzed how urban form characteristics can have different environmental impacts by influencing more or less sustainable mobility patterns. However, most of these studies present empirical analysis without considering a theoretical understanding regarding the causal paths between urban form and mobility patterns. Moreover, this literature focuses mostly on cities in the Global North, and there is much less evidence about the relationship between urban form and sustainable mobility in the Global South and particularly in Brazil. In this study, we examine the extent to which the urban form of Brazilian cities impacts their urban mobility energy consumption. First, we present a descriptive analysis of how urban areas in Brazil have developed spatially between 1990 and 2015. Next, we use regression models to analyze the extent to which the amount of energy per capita used in private motorized transport in the 182 largest urban areas in Brazil are affected by different characteristics of urban form (population density, land use mix, compacity, contiguity, as well as the intersection density, closeness centrality and circutity of road networks). The regression models are built based upon a Directed Acyclic Graph (DAG) that we propose to map the causal paths between urban form and transport energy use based on an extensive literature review. We found that there was a general increase in population density in all cities between 1990 and 2015. However, medium-size cities became more sprawled and fragmented while large cities became slightly more compact and contiguous. Our regression results show that higher levels of land use mix, population density and compacity lead to lower transport energy use. Moreover, the effect of compacity varies by population size in a way that higher compacity levels lead to higher energy consumption in large cities, possibly reflecting diseconomies of agglomeration. These findings have broader implications that show the need for more integrated local land use and transport policies in shaping less car-dependent cities and more sustainable mobility patterns.
10419/284859
Keywords: R11; R40; R42; R49; R52; R58; N76; 330; urban form; sustainable mobility; transport energy; Brazil